2009
DOI: 10.1503/cmaj.081777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal multimicronutrient supplementation on pregnancy outcomes: a meta-analysis

Abstract: N utrition plays an important role in the growth and development of the fetus. Studies of the nutritional status of pregnant women during the Dutch famine revealed increased risks of infertility, abortion, fetal intrauterine growth restriction and perinatal mortality among malnourished women.1 In many parts of the world, a similar situation exists for many pregnant women with respect to nutrition. Overall, the diet of pregnant women has been reported to be deficient in calories and micronutrients. 2 Both macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 25 publications
7
64
1
4
Order By: Relevance
“…The benefits of prenatal multiple micronutrient supplementation on birth size, neonatal morbidity and mortality and later growth have also been shown in studies conducted in other developing countries (35)(36)(37)(38)(39) . In one meta-analysis, reduction of LBW was found among infants of mothers prenatally supplemented with multiple micronutrients compared with placebo or Fe and folic acid (40) , whereas other meta-analyses or reviews concluded no added benefits of multiple micronutrient or Zn supplementation on birth weight (41,42) . The interpretation of these results, in relation to ours, is that composition and dosage of micronutrients as well as the time during pregnancy when supplements are introduced are crucial for infant growth and may explain the differences seen with different micronutrient and supplementation regimes.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of prenatal multiple micronutrient supplementation on birth size, neonatal morbidity and mortality and later growth have also been shown in studies conducted in other developing countries (35)(36)(37)(38)(39) . In one meta-analysis, reduction of LBW was found among infants of mothers prenatally supplemented with multiple micronutrients compared with placebo or Fe and folic acid (40) , whereas other meta-analyses or reviews concluded no added benefits of multiple micronutrient or Zn supplementation on birth weight (41,42) . The interpretation of these results, in relation to ours, is that composition and dosage of micronutrients as well as the time during pregnancy when supplements are introduced are crucial for infant growth and may explain the differences seen with different micronutrient and supplementation regimes.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that improved immune function may reduce the risk of infection thereby preventing preterm delivery; they may also improve energy metabolism and anabolic processes leading to a decrease in IUGR prevalence as well as improving the maternal response to stress (Shah and Ohlsson 2009). However, there is insufficient evidence attributing a deficiency of a specific nutrient to an adverse pregnancy outcome (Keen et al 2003).…”
Section: Supplementationmentioning
confidence: 99%
“…Even though the direct translation of this research to humans is unclear, intake of multivitamin supplements during pregnancy in developed countries is likely to result in intakes greater than the recommended quantities (Shah and Ohlsson 2009). In addition, the safety and effectiveness of vitamin A and D supplementation specifically have been questioned.…”
Section: Significancementioning
confidence: 99%